Connecting Mixed Methods as an Education Research Strategy - Rebecca Blanchard; Jack Scott (Association of American Medical Colleges, 2014)
Abstract This faculty and professional development instructional module is intended for medical education researchers seeking to combine qualitative and quantitative research methods. The module is particularly useful when investigating a particular phenomenon or challenging educational practice. The case-based approach guides participants through an interactive, small-group plan of action on a relevant research topic. The team-building activity, although representative, may be easily modified for site-specific education research needs. We recommend incorporating this instructional module during the initial phases of an organizational strategic plan in education research among interprofessional healthcare providers. This process includes a worksheet for designing a research project or study. A post-activity debriefing reinforces strategies to overcome barriers or challenges in education research design that incorporate elements of qualitative and quantitative methodologies. The instructional module concludes with practical considerations in implementing mixed methods from the relevant medical education literature. The enclosed resource files provide professional development facilitators with a turn-key approach when organizing and conducting a mixed-methods education research workshop. Therefore, we offer goals and strategies for effective mixed-methods research that are attainable through educational development. Evaluations of this workshop were positive, respondents indicated it was a "Good introduction for a novice in medical education," and that "Designing a faux study was a very useful exercise."